Medical cost and healthcare utilization of amyotrophic lateral sclerosis in China: A cohort study based on hospital data from 2015 to 2018. Issue 47 (20th November 2020) - Song, Han; Liu, Jian-Chao; Cao, Zi-Peng; Luo, Wen-Jing; Chen, Jing-Yuan
Abstract : Abstract: Amyotrophic lateral sclerosis (ALS), a specific neurodegenerative disease, imposed increased economic and utilizations burden on the healthcare system, especially with the progress of the diseases severity. However, the economic burden on Chinese ALS patients remained unclear. This study therefore was aimed to investigate medical cost and healthcare utilization for Chinese ALS patients. Longitudinal health data of over 20 million individuals, including military personnel and civilians, was collected from all Chinese military hospitals. We identified 480 patients with a first major diagnosis for ALS from 2015 to 2018, while matched 400 controlled patients on age, gender, ethnic group, geographic region, length of stay, year of diagnosis and comorbidity. Their medical cost and healthcare utilizations were then measured 1 year before, and 1 year after ALS diagnosis. The median annual medical cost of ALS patients was about 2-fold higher, 17, 087 CNY during the index year than 1 year before, 7859 CNY. The highest increase in utilizations may account for medical costs on ALS patients, which was represented by hospitalizations (Odd Ratio (OR) = 4.26, 95% confidence interval (CI) 3.52, 5.15), electromyography (OR = 4.14, 95% CI 2.37, 7.22), nerve conduction velocity (OR = 3.26, 95% CI 2.23, 4.77). This study is the first one reporting direct economic burden on Chinese ALS patients. Efforts should be made to develop cost-effective diagnostic tools in order that sources of medical cost were more effectively allocated, and this disease was detected earlier.